Diurnal variation in swim performance remains, irrespective of training once or twice daily - Martin, L.; Nevill, A. M.; Thompson, K. G. (International Journal of Sports Physiology and Performance, 2007)
Fast swim times in morning rounds are essential to ensure qualification in evening finals. A significant time-of-day effect in swimming performance has consistently been observed, although physical activity early in the day has been postulated to reduce this effect. The aim of this study was to compare intradaily variation in race-pace performance of swimmers routinely undertaking morning and evening training (MEG) with those routinely undertaking evening training only (EOG). Methods: Each group consisted of 8 swimmers (mean ± SD: age = 15.2 ± 1.0 and 15.4 ± 1.4 y, 200-m freestyle time 132.8 ± 8.4 and 136.3 ± 9.1 s) who completed morning and evening trials in a randomized order with 48 h in between on 2 separate occasions. Oral temperature, heart rate, and blood lactate were assessed at rest, after a warm-up, after a 150-m race-pace swim, and after a 100-m time trial. Stroke rate, stroke count, and time were recorded for each length of the 150-m and 100-m swims. Results: Both training groups recorded significantly slower morning 100-m performances (MEG = +1.7 s, EOG = +1.4 s; P < .05) along with persistently lower morning temperatures that on average were -0.47°C and -0.60°C, respectively (P < .05). No differences were found in blood-lactate, heart-rate, and stroke-count responses (P > .05). All results were found to be reproducible (P > .05). Conclusions: The long-term use of morning training does not appear to significantly reduce intradaily variation in race-pace swimming or body temperature.